Migration and the Welfare State: The Economic Power of the Non-Voter? - Kira Boerner; Silke Uebelmesser (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
This paper investigates the impact of emigration on the political choice regarding the size of the welfare state. Mobility has two countervailing effects: the political participation effect and the tax base effect. With emigration, the composition of the constituency changes. This increases the political influence of the less mobile part of the population. The new political majority has to take into account that emigration reduces tax revenues and thereby affects the feasible set of redistribution policies. The interaction of the two effects has so far not been analyzed in isolation. We find that the direction of the total effect of migration depends on the initial income distribution in the economy. Our results also contribute to the empirical debate on the validity of the median-voter approach for explaining the relation between income inequality and redistribution levels.
urn:nbn:de:bvb:19-epub-728-4
Keywords: F22; H50; D31; D72; 330; migration; redistribution; voting